2011
DOI: 10.1186/1742-4690-8-48
|View full text |Cite
|
Sign up to set email alerts
|

A stabilized HIV-1 envelope glycoprotein trimer fused to CD40 ligand targets and activates dendritic cells

Abstract: BackgroundOne reason why subunit protein and DNA vaccines are often less immunogenic than live-attenuated and whole-inactivated virus vaccines is that they lack the co-stimulatory signals provided by various components of the more complex vaccines. The HIV-1 envelope glycoprotein complex (Env) is no exception to this rule. Other factors that limit the induction of neutralizing antibodies against HIV-1 lie in the structure and instability of Env. We have previously stabilized soluble trimeric mimics of Env by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
56
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(60 citation statements)
references
References 64 publications
4
56
0
Order By: Relevance
“…Note that the internal D7324 epitope in the C5 domain of SOSIP constructs is mutated by the introduction of the cysteine at residue 501 that forms the intramolecular disulfide bond with gp41 and that it is also occluded by the proximity of the gp41 subunit; hence, unmodified SOSIP gp140s do not react efficiently with D7324 (6,83). Because of the addition of C-terminal sequences to SOSIP gp140, SOSIP.R6-IZ-D7324 trimers are poorly cleaved (63).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Note that the internal D7324 epitope in the C5 domain of SOSIP constructs is mutated by the introduction of the cysteine at residue 501 that forms the intramolecular disulfide bond with gp41 and that it is also occluded by the proximity of the gp41 subunit; hence, unmodified SOSIP gp140s do not react efficiently with D7324 (6,83). Because of the addition of C-terminal sequences to SOSIP gp140, SOSIP.R6-IZ-D7324 trimers are poorly cleaved (63).…”
Section: Methodsmentioning
confidence: 99%
“…We introduced (i) a disulfide bond between residues 501 in gp120 and 605 in gp41 (A501C, T605C) (6); (ii) a trimer-stabilizing substitution in gp41 (I559P) (83); and (iii) a sequence-enhanced site for furin cleavage (RRRRRR) (7). We further modified the JR-FL SOSIP.R6 gp140 construct to include a C-terminal GCN4-based trimerization domain (isoleucine zipper [IZ]) (30,63). We have shown that this domain further improves trimer stability.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…7, D and F). Thus, CPP or another molecule such as the CD40 ligand (61) can be oriented at the quasi-2-fold axes for targeting of the nanoparticle to antigen presenting cells such as the dendritic cells.…”
Section: Display Of Gp41 Trimers On the Bacteriophage T4mentioning
confidence: 99%